Gambaran Pemberian Obat pada Pasien Penyakit ISPA di Puskesmas Harapan Raya Kota Pekanbaru - Novia Sinata; Indah Wahyuni; Intan Ayu Deswinda; Maisarah Maisarah; Marisa Nurlita (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Acute Respiratory Infection (ARI) is a significant public health issue, particularly in areas with suboptimal environmental conditions. Community Health Centers (Puskesmas), as the primary healthcare providers, play a crucial role in managing ARI cases. This study aims to analyze the prescribing patterns of medications for ARI patients at Pekanbaru Community Health Center to evaluate whether the prescribed treatments adhere to existing guidelines and to provide recommendations. The sample for this study comprises ARI patients who sought treatment at Pekanbaru Community Health Centers in March 2024. Secondary data from the monthly report of Pekanbaru Community Health Centers in March 2024 was used as the research instrument. The collected data was analyzed by calculating the percentage of medication usage. Based on the findings from Pekanbaru Community Health Centers, the following conclusions were drawn: Most patients consuming ARI medications were female, with 80 respondents, compared to 70 males. The age group with the highest number of ARI medication consumers was [missing data]. Paracetamol 500mg was the most commonly prescribed medication at the health center.